Association Between Walking Energetics and Fragmented Physical Activity in Mid- to Late-Life. (8th May 2021) - Liu, Fangyu; Wanigatunga, Amal A; Kuo, Pei-Lun; Zipunnikov, Vadim; Simonsick, Eleanor M; Ferrucci, Luigi; Schrack, Jennifer A
Abstract: Background: Physical activity becomes increasingly fragmented with age, which may be an early marker of functional decline. Energetic cost of walking and energy capacity are also linked with functional decline, but their associations with activity fragmentation, and the potential modifying roles of total daily physical activity and age, remains unclear. Method: A total of 493 participants (50–93 years) from the Baltimore Longitudinal Study of Aging underwent measures of energetic cost of usual-paced overground walking (mL/kg/m), energy demand during slow walking (mL/kg/min) on a treadmill (0.67 m/s, 0% grade), and average peak walking energy expenditure (mL/kg/min) during a fast-paced 400-m walk. A ratio of slow walking to peak walking energy expenditure ("cost-to-capacity ratio") was calculated. Activity fragmentation was quantified as an active-to-sedentary transition probability (ASTP) using Actiheart accelerometer data. Linear regression models with ASTP as the dependent variable were used to test whether poorer energy cost and capacity were associated with higher ASTP and whether the associations differed by daily physical activity or age. Results: After adjusting for demographics, body composition, comorbidities, and daily physical activity, every 10% higher cost-to-capacity ratio was associated with 0.4% greater ASTP ( p = .005). This association was primarily driven by the least active participants ( p interaction = .023). Peak walking energy expenditure was only associated with ASTP among participants aged ≥70 years. Conclusions: Higher cost-to-capacity ratio and lower energy capacity may manifest as more fragmented physical activity, especially among those less active or aged ≥70 years. Future studies should examine whether an increasing cost-to-capacity ratio or declining energy capacity predicts subsequent activity fragmentation.